Bipartite Industrial Relations Dispute Settlement Counseling At Pt Asri Jewel Villas And Spa - Adiwidya, I Made; Wirantini, Ni Kadek Ayu (Abdi Masyarakat, 2025)
This Community Service aims to provide understanding to workers and employers at PT Asri Jewel Villa and Spa regarding the resolution of industrial relations disputes, especially bipartite. The location of the community service was chosen deliberately, on the grounds that PT Asri Jewel Villa and Spa is a company engaged in the tourism sector where disputes between workers and employers are very vulnerable considering that Bali is a world tourist destination that requires workers in the tourism sector to work professionally. The target audience for this Community Service activity is workers and employees at PT Asri Jewel Villa and Spa, totaling 26 people, one entrepreneur and 25 workers. In this Community Service, data is analyzed using qualitative analysis, namely the data and facts found will be described. The results obtained from the community service activity of bipartite dispute resolution counseling for workers and employers at PT Asri Jewel Villas and Spa are increased insight and knowledge of counseling participants regarding the resolution of industrial relations disputes, especially settlements without a third party. With this counseling, workers and employers can understand the legal aspects and mechanisms of bipartite dispute resolution. This allows for faster resolution of disputes between workers and employers.